Terahertz Transmission Characteristics of Double-Layer Plasmonic Metamaterial and LC-Based Structure - Yang, Jun; Xu, Junjie; Mao, Rongxin; Li, Ying; Yin, Zhiping; Deng, Guangsheng; Cai, Fei (Frontiers in Materials, 2021)
In this paper, we present a novel design of an electrically tunable metamaterial device in the terahertz frequency range of 325–500 GHz. The device is analyzed and optimized using an equivalent circuit and numerical simulation. The experimental and simulation results are almost identical in the entire design frequency range. A maximum modulation depth and a minimum insertion loss of 90.8% and 0.79 dB are achieved in the transmission window, respectively. The center frequency of the passband is shifted to the left by 35.19 GHz, and the bandpass width decreases from 103.43 GHz to 37.6 GHz as the bias voltage increases from 0 to 30 V. This structure provides new insights into the potential of electrically tunable terahertz devices for a wide range of applications.